PROBLEMATIKA PERILAKU PEDAGANG PASAR TRADISIONAL: STUDI PERSPEKTIF ETIKA BISNIS ISLAM - Sakur Sakur; Ah. Ali Arifin; Iqbal Rafiqi (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
The traditional market is a market that is identical to a market that has experienced a steady decline, resulting in a market that has an impact on unfair competition, lack of legal protection, congestion, the market looks dirty and, and is prone to accidents that occur. Therefore, Islamic business ethics plays a very important role in regulating the behavior of traders. The formulation of the problem in this research is first, the behavior of traditional market participants in the problem in the market on 17 August Pamekasan?. Second, how are the government's efforts in responding to the behavior of traditional market players in guarding the market on 17 August Pamekasan?. Third, what is the perspective of Islamic business ethics on the behavior of traditional market traders in guarding the market on 17 August Pamekasan? This study uses an approach with a descriptive type of research. Sources of data obtained through interviews, observation, and documentation. Checking the validity of the data using persistence, reference materials and additional observations. The results of the study show that, First: The behavior of traditional market participants in the August 17 market in maintaining still lacks care, often violates and is stubborn, Second: The government's efforts in responding to the behavior of market traders on August 17 have been good but in practice it is still lacking, third: According to an ethical perspective Islam on the behavior of traditional market participants in guarding the market on August 17, Pamekasan in terms of the principle of monotheism, the principle of balance (justice/equilibrium), the principle of free will (ikhtiar/free will), the principle of responsibility (responsibility) and the principle of responsibility (Ihsan) are still not yet fully implemented by traders.